Activated steady status and distinctive FcεRI-mediated responsiveness in basophils of atopic dermatitis - Shinya Imamura; Ken Washio; Mayuko Mizuno; Yoshiko Oda; Atsushi Fukunaga; Chikako Nishigori (Allergology International, 2021)
Background: Although basophils are considered to play an important role for maintenance of type 2 inflammation in atopic dermatitis (AD), studies on basophils in AD patients are limited. Some studies have reported the activation status, including CD203c and CD63, of peripheral blood basophils in AD patients. Methods: We examined the features of circulating basophils in AD patients, assessed cell surface marker expressions and total serum IgE, and compared basophil responsiveness to stimulation between AD patients and healthy controls (HCs). In addition, the correlations among AD severity, laboratory factors, and features of basophils were examined. Blood samples from 38 AD patients and 21 HCs were analyzed. Basophil response markers CD203c and CD63, and expression of surface-bound IgE and FcεRI on basophils were measured. CD203c and CD63 expressions induced by stimulation with anti-IgE and anti-FcεRI antibodies were measured. Clinical/laboratory factors including total serum IgE were examined for correlations with these basophil parameters. Results: Baseline CD203c and CD63 expression on basophils were significantly higher in AD patients compared with HCs. The CD203c/CD63 response ratio to anti-FcεRI stimulation was higher than that to anti-IgE stimulation in AD patients, but not HCs. FcεRI expression on basophils was higher in AD patients than in HCs, although surface-bound IgE on basophils was equivalent. Total serum IgE had negative correlations with surface-bound IgE and CD63 responsiveness to anti-IgE stimulation. Conclusions: Basophils were spontaneously activated under steady-state conditions in AD patients and responsiveness to anti-IgE stimulation was lower than in HCs. Despite high serum IgE and high basophil FcεRI expression, surface-bound IgE on basophils remained relatively low. Basophils might be suppressed or exhausted regarding FcεRI signaling via IgE in severe AD.